The role of the left ventral occipitotemporal cortex in speech processing—The influence of visual deprivation - Dziȩgiel-Fivet, Gabriela; Beck, Joanna; Jednoróg, Katarzyna (Frontiers in Human Neuroscience, 2023)
The role of the left ventral occipitotemporal cortex (vOT) in reading is well established in both sighted and blind readers. Its role in speech processing remains only partially understood. Here, we test the involvement of the left vOT in phonological processing of spoken language in the blind (N = 50, age: 6.76 – 60.32) and in the sighted (N = 54, age: 6.79 – 59.83) by means of whole-brain and region-of-interest (including individually identified) fMRI analyses. We confirm that the left vOT is sensitive to phonological processing (shows greater involvement in rhyming compared to control spoken language task) in both blind and sighted participants. However, in the sighted the activation was observed only during rhyming task and in the speech-specific region of the left vOT, pointing to task and modality specificity. In contrast, in the blind group, the left vOT was active during speech processing irrespective of task and in both speech and reading-specific vOT regions. Only in the blind, the left vOT presented a higher degree of sensitivity to phonological processing than other language nodes in the left inferior frontal and superior temporal cortex. Our results suggest a changed development of the left vOT sensitivity to spoken language, resulting from visual deprivation.